1986
DOI: 10.1007/bf00205649
|View full text |Cite
|
Sign up to set email alerts
|

Tumor therapy of neoplastic diseases with tumor cells and neuraminidase

Abstract: The therapeutic effect of i.d. injection of tumor cells mixed with Vibrio cholerae neuraminidase (VCN) on tumor progression in dogs with spontaneous mammary tumors was investigated. The i.d. injections were performed in a chessboard-like manner: different numbers (10(5), 10(6), 10(7), and 10(8) of mitomycin-treated autologous tumor cells (M-TC) were each mixed with different amounts (10, 50, and 100 mU) of VCN. These different mixtures were injected i.d. at different sites in dogs on the day of resection of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, one study reported that combining intratumoral injection of BCG cell walls with surgery increased survival time over surgery alone [28]. Another study reported that canine mammary tumor cells treated with neuraminidase and used as a vaccine had antitumor activity in dogs [29].…”
Section: Canine Mammary Neoplasmsmentioning
confidence: 99%
“…However, one study reported that combining intratumoral injection of BCG cell walls with surgery increased survival time over surgery alone [28]. Another study reported that canine mammary tumor cells treated with neuraminidase and used as a vaccine had antitumor activity in dogs [29].…”
Section: Canine Mammary Neoplasmsmentioning
confidence: 99%
“…Aqueous ammonia transformed 10 into 13 (0"; J(2,3) = 5.8 Hz, J(3,4) = 3.8 Hz) and, hence, into the addition products (r.t.), which were directly converted into a mixture of the anomeric D-alrro -imines 14 …”
Section: J(34) = 80 Hzmentioning
confidence: 99%
“…In pneumococcal and clostridial infections, high concentrations of sialidases in wounds and body fluids have been found [12] [13]. The role of sialidases -particularly those of Vibrio cholerae -in cancer and cancer therapy is unclear and controversial [14]. Selective inhibition of sialidases might, therefore, be a target for biochemical studies and clinical applications, particularly in view of the preparation of antiviral [ 151, antibacterial, and antiprotozoal drugs.…”
mentioning
confidence: 99%
“…Responses were infrequent and transient in nature (Sedlacek et al . , ). In another study, dogs with advanced CMC were treated with autologous tumour cell membranes that had been conjugated to bovine gamma globulins, but progression of disease was unaffected (Hannant et al .…”
Section: Cancer Vaccinesmentioning
confidence: 99%